Chemical Procedures for Paint Removal in Used Thermoplastics for Revalorization as a Raw Material in the Automotive Industry - Carla Zambrano Membrives; Pablo Tamarit; Ana Inés Fernandez; Camila Barreneche (Advances in Polymer Technology)
The recycling of thermoplastic polymers from end-of-life vehicles is crucial to achieve a circular economy within the sector and prevent the accumulation of plastic waste by reusing it. However, several challenges in these processes present difficulties, making it challenging or impossible to recycle these materials for the same applications, impeding the closure of the life cycle and valorization of waste. The primary problem faced by plastic converters is the presence of superficial paint. In this study, we evaluate the implementation of chemical methods with varying conditions to remove paint from used bumpers thermoformed with polypropylene, with the aim of valorizing the plastic waste from these bumpers. We examine the various process variables, such as reagent concentration, temperature, time, and pH. Additionally, we analyze procedures to quantify the paint content in the different recycled samples and use this as a tool to compare the effectiveness of different paint removal processes.